2002
DOI: 10.1097/00043426-200202000-00010
|View full text |Cite
|
Sign up to set email alerts
|

No Major Cognitive Impairment in Young Children With Acute Lymphoblastic Leukemia Using Chemotherapy Only: A Prospective Longitudinal Study

Abstract: Children surviving ALL have no major cognitive impairment after chemotherapy, including intrathecal and high-dose intravenous methotrexate. The slightly better outcome in the current group may indicate possible adverse effects of more dexamethasone treatment in the previous group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 21 publications
8
63
0
Order By: Relevance
“…27,28,[31][32][33][34] The other 4 studies used a longitudinal design, identified patients at diagnosis, and completed periodic neurocognitive assessments during treatment and off therapy. 11,19,29,30 Collectively, the study population included in the analyses had a mean age at diagnosis of 4.4 years (median, 4.0), a mean age at last evaluation of 11.7 years (median, 10.3), and a mean time since diagnosis of 8.0 years (median, 8.2). Four studies had a mean time since diagnosis of less than 6 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28,[31][32][33][34] The other 4 studies used a longitudinal design, identified patients at diagnosis, and completed periodic neurocognitive assessments during treatment and off therapy. 11,19,29,30 Collectively, the study population included in the analyses had a mean age at diagnosis of 4.4 years (median, 4.0), a mean age at last evaluation of 11.7 years (median, 10.3), and a mean time since diagnosis of 8.0 years (median, 8.2). Four studies had a mean time since diagnosis of less than 6 years.…”
Section: Resultsmentioning
confidence: 99%
“…Intelligence or overall cognitive ability was measured by 8 studies. 11,19,28,[30][31][32][33] IQ was measured and assessed across 3 dimensions of the Wechsler Intelligence Scales (version dependent on age of patient): FSIQ, VIQ, and PIQ. For FSIQ, 432 ALL survivors met eligibility to be included in the treatment group and were compared with 465 healthy control subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cranial radiation is associated with more severe neurocognitive impairment than that conferred by systemic and intrathecal chemotherapy. 20,[27][28][29] As previously discussed, our study overcame many of the limitations of the Waber et al study. 26 Our overall results are consistent with smaller studies based on patients with ALL.…”
Section: Discussionmentioning
confidence: 96%
“…Kingma et al found normal cognitive functioning but "lower test scores in patients compared with controls in the test of attention, speed, sequencing, mental flexibility, and visual search" (8). Lofstad et al found that even though "the cognitive outcome for children with ALL treated with chemotherapy only was in the normal range, it represented a substantial decrease of as much as one standard deviation compared to matched healthy controls" (9).…”
Section: Introductionmentioning
confidence: 99%